2017
DOI: 10.7717/peerj.4164
|View full text |Cite
|
Sign up to set email alerts
|

Information from dynamic length changes improves reliability of static ultrasound fascicle length measurements

Abstract: PurposeVarious strategies for improving reliability of fascicle identification on ultrasound images are used in practice, yet these strategies are untested for effectiveness. Studies suggest that the largest part of differences between fascicle lengths on one image are attributed to the error on the initial image. In this study, we compared reliability results between different strategies.MethodsStatic single-image recordings and image sequence recordings during passive ankle rotations of the medial gastrocnem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The efficacy of this is demonstrated by the very strong agreement between manual and automatic measurements (CMC > 0.94) and low RMES for fascicle length (RMSE = 3.31 ± 1.53 mm) and pennation angle RMSE = 4.12° ± 1.98°). The improvement of tracking due to supervision is supported by the work of Aeles et al (2017) where they observed that providing examiners with the ability to watch the video prior to fascicle identification improved the reliability of fascicle identification.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The efficacy of this is demonstrated by the very strong agreement between manual and automatic measurements (CMC > 0.94) and low RMES for fascicle length (RMSE = 3.31 ± 1.53 mm) and pennation angle RMSE = 4.12° ± 1.98°). The improvement of tracking due to supervision is supported by the work of Aeles et al (2017) where they observed that providing examiners with the ability to watch the video prior to fascicle identification improved the reliability of fascicle identification.…”
Section: Discussionmentioning
confidence: 93%
“…In our data, we did not observe very much fascicle curvature, even in fully contracted state. Fascicles in the gastrocnemius do not curve as much as fascicles in other muscles such as the vastus medialis (Gillett, Barrett & Lichtwark, 2013) or the biceps femoris (Seymore et al, 2017; Aeles et al, 2017). If significant amount of fascicle curvature is observed, we suggest that users exercise judgment as to whether this straight-line approximation is valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this method only holds true when the muscle fascicles act in the same 2D plane as our ultrasound image. However, good reliability and accuracy has been proven previously (1,2,48).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for this offset is the variability in fascicle segmentation on the first image of each ultrasound scanning sequence. A recent analysis of the reliability of fascicle tracking ( Aeles et al, 2017 ) found good reliability for the analysis of fascicle length changes but also pointed at the more variable segmentation of the initial image, rendering the comparison of absolute lengths more challenging. However, in the present study, the same investigator (AW) analyzed all images in a random order and the fact that no differences in fascicle length at touch down were found in the control group support these findings.…”
Section: Discussionmentioning
confidence: 99%